2009
DOI: 10.5338/kjea.2009.28.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Application Rate on Growth and Yields of Aster scaber Thunb. and Ligularia fischeri Turcz. in the First Year after Transplanting

Abstract: Chinese cabbage cultivation has been typically practiced in alpine sloped farmland in Gangwon province, and caused severe soil erosion by soil disturbance like tillage. Cultivation of wild edible greens such as Aster scaber Thunb. and Ligularia fischeri Turcz. could be one of alternative ways to reduce soil erosion, because their residues become stubble mulch after harvest, and there is no need for tillage every year. Therefore, the objective of this research was to estimate the effect of nitrogen application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Soils by test site showed weak acidity (pH 5.59-6.52) regardless of region (Table 3). The acidity was higher than that of general forest soil, which was higher than the pH of the soil where Aster scaber Thunb and Ligularia fischeri are cultivated (pH 5.2) (Choi et al, 2009). The major components shown in the study results of upland soil of cultivation sites for Aster scaber Thunb and Ligularia fischeri are as follows (Choi et al 2009).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Soils by test site showed weak acidity (pH 5.59-6.52) regardless of region (Table 3). The acidity was higher than that of general forest soil, which was higher than the pH of the soil where Aster scaber Thunb and Ligularia fischeri are cultivated (pH 5.2) (Choi et al, 2009). The major components shown in the study results of upland soil of cultivation sites for Aster scaber Thunb and Ligularia fischeri are as follows (Choi et al 2009).…”
Section: Resultsmentioning
confidence: 82%
“…The acidity was higher than that of general forest soil, which was higher than the pH of the soil where Aster scaber Thunb and Ligularia fischeri are cultivated (pH 5.2) (Choi et al, 2009). The major components shown in the study results of upland soil of cultivation sites for Aster scaber Thunb and Ligularia fischeri are as follows (Choi et al 2009). Due to phosphoric manure fertilization, the available phosphate in upland soil was 6-20 times higher than that in forest land.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Improving soil physicochemical properties is known to increase the activity of effective microorganisms and soil nutrient availability, thereby promoting aboveground crop growth [42,52]. Additionally, Choi et al (2009) reported that A. scaber treated with 120 kg•ha −1 nitrogen yielded 88.0% more than the control that did not receive any fertilization, implying that as a leafy forest product, increased nitrogen content in aboveground growth can be directly related to growth and yield. Such findings were also found in the other forest crops e.g., Ligularia fischeri Turcz.…”
Section: Growth Characteristicsmentioning
confidence: 99%
“…Recently, pharmacological effects in lowering cholesterol and anticancer have been associated with this herb [22,23]. Nonetheless, it has been reported that A. scaber is a nutrient-demanding species, with increased yields and growth at higher nitrogen fertilization rates [24].…”
Section: Introductionmentioning
confidence: 99%